Prognostic significance of ALK high expression in SCLC: a 9-year cohort analysis - Xu, Jinhe; Zhang, Wenting; Xie, Feilai; Wang, Chenxi; Cheng, Feng; Rao, Ruiying; Chen, Ying; Zhang, Lei; Wen, Wen; Zhao, Zhongquan; Yuan, Jialing; Zheng, Yuqin; et al. (Frontiers in Oncology, 2025)
PurposeThe aim of this study was to investigate the prognostic value of the abnormal expression of anaplastic lymphoma kinase (ALK) protein in patients with small cell lung cancer (SCLC) based on 9-year data from our center.MethodsA retrospective cohort study was conducted to assess the clinical outcomes of patients with ALK-positive SCLC diagnosed in our hospital over the past 9 years. We used public databases to analyze the expression of ALK in pan-cancer and its prognostic value and analyzed the correlation between ALK and SCLC prognosis-related genes.ResultsA total of 685 patients diagnosed with SCLC underwent ALK testing, and 59 patients were identified to have abnormal expression of the ALK protein, with 10 cases showing strong expression, 14 cases displaying moderate expression, and 35 cases exhibiting weak expression. The median age of the ALK-positive cohort was 64 years (range: 58–70 years), 91.5% (54/59) were male, 61.0% (36/59) were smokers, and the median overall survival (mOS) was 7.0 months (95% CI: 4.5–9.5 months). Within this cohort, the mOS for the ALK (+) subgroup was 4.0 months (95% CI: 2.9–5.1 months), the mOS for the ALK (++) subgroup was 10.0 months (95% CI: 4.9–15.1 months), and the mOS for the ALK (+++) subgroup was 12.0 months (95% CI: 7.4–16.6 months). Kaplan–Meier revealed that the mOS of the ALKLow group was significantly worse than that of the ALKHigh group [mOS: 4.0 months (95% CI: 2.9–5.1 months) versus 11.0 months (95% CI: 8.3–13.7 months), p = 0.009]. Following covariate adjustment using a Cox regression model, it was indicated that the level of abnormal expression of the ALK protein was an independent prognostic factor for patients with SCLC (HR: 0.486, 95% CI: 0.271–0.871, p = 0.015).ConclusionThe prognosis for patients with SCLC with strong abnormal expression of the ALK protein was significantly better than those with weak expression.